PENGARUH GREEN MARKETING, LABEL HALAL DAN BRAND AMBASSADOR TERHADAP KEPUTUSAN BELANJA KONSUMEN PRODUK WARDAH (Studi Empiris Kota Makassar) - Febriyanti Jumat; Ratna Dewi; Aditya Halim Perdana Kusuma (Center of Economic Students Journal, 2023)
This study aims to assess and explain the influence of Green Marketing, Halal Label and Brand Ambassador on Consumer Shopping Decisions for Wardah products in Makassar City. Sampling using the lameshow formula with the results of 96 respondents who were the samples in this study, the type of research used in this study is quantitative research. The sampling technique used in this study uses the Purposive Sampling technique, this method is a sampling determination technique with certain considerations, this technique is one of the Nenprobability Sampling techniques where the sample collection technique does not provide equal opportunities or opportunities for each population to become a sample. The data analysis technique used in this study uses multiple linear regression analysis. The multiple linear regression equation obtained is Y = - 0.030 + 0.209X1 + 0.226X2 + 0.578X3 + e. Partially there is an influence of Green Marketing, Halal Label and Brand Ambassador on Shopping Decisions with a significance value of less than 0.05. The R Square value obtained is 0.898 showing that Green Marketing, Halal Label and Brand Ambassador influence the Shopping Decision of Wardah product consumers by 89.8% and the rest is influenced by other factors not included in the study. The results of the study indicate that the variables Green Marketing, Halal Label and Brand Ambassador have a positive and significant influence on the Shopping Decision of Wardah product consumers in the city of Makassar